Theology of the Old Testament - Hinson, David F. (David Francis) (London S.P.C.K., 1976)
In this final volume of Hinson's three-part Old Testament introduction, he argues that all that happened in Old Testament times was a preparation for the coming of Christ. As in all books in the series, the text is supported with suggestions for further study and topics for discussion
Keywords: Bible. -- Old Testament -- Theology. Bible. -- Old Testament. Bibel -- Altes Testament